2000
DOI: 10.1073/pnas.110587497
|View full text |Cite
|
Sign up to set email alerts
|

Genome evolution of wild barley ( Hordeum spontaneum ) by BARE -1 retrotransposon dynamics in response to sharp microclimatic divergence

Abstract: The replicative spread of retrotransposons in the genome creates new insertional polymorphisms, increasing retrotransposon numbers and potentially both their share of the genome and genome size. The BARE-1 retrotransposon constitutes a major, dispersed, active component of Hordeum genomes, and BARE-1 number is positively correlated with genome size. We have examined genome size and BARE-1 insertion patterns and number in wild barley, Hordeum spontaneum, in Evolution Canyon, Lower Nahal Oren, Mount Carmel, Isra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
393
3
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 541 publications
(428 citation statements)
references
References 50 publications
(63 reference statements)
22
393
3
6
Order By: Relevance
“…Most previous studies of genetic diversity of wild barley in EC1 found a higher level of genetic diversity at SFS than NFS based on allozymes, DNA sequences of single genes (Yang et al, 2009) and copy number of BARE-1 retrotransposons (Kalendar et al, 2000). In contrast, REMAP (Retrotransposons-Microsatellite Amplified Polymorphism) analyses revealed more genotypes in the NFS than the SFS (Kalendar et al, 2000). Likewise, SSRs revealed a higher genetic diversity on the NFS than the SFS (Nevo et al, 2005).…”
Section: Genetic Variation Of Wild Barley In Ec1mentioning
confidence: 80%
See 2 more Smart Citations
“…Most previous studies of genetic diversity of wild barley in EC1 found a higher level of genetic diversity at SFS than NFS based on allozymes, DNA sequences of single genes (Yang et al, 2009) and copy number of BARE-1 retrotransposons (Kalendar et al, 2000). In contrast, REMAP (Retrotransposons-Microsatellite Amplified Polymorphism) analyses revealed more genotypes in the NFS than the SFS (Kalendar et al, 2000). Likewise, SSRs revealed a higher genetic diversity on the NFS than the SFS (Nevo et al, 2005).…”
Section: Genetic Variation Of Wild Barley In Ec1mentioning
confidence: 80%
“…The three clusters obtained with STRUCTURE differ in their level of genetic diversity, and the NFS accessions are about two times more diverse than the SFS accessions. Most previous studies of genetic diversity of wild barley in EC1 found a higher level of genetic diversity at SFS than NFS based on allozymes, DNA sequences of single genes (Yang et al, 2009) and copy number of BARE-1 retrotransposons (Kalendar et al, 2000). In contrast, REMAP (Retrotransposons-Microsatellite Amplified Polymorphism) analyses revealed more genotypes in the NFS than the SFS (Kalendar et al, 2000).…”
Section: Genetic Variation Of Wild Barley In Ec1mentioning
confidence: 81%
See 1 more Smart Citation
“…(12,13) have suggested that natural selection could be involved in regulating genome size, although a change in size is primarily due to the genome's tolerance for repeated sequences (5) and its ability to mobilize them (14). Intra-species variation in genome size has also been shown to be associated with environmental conditions in plants, and seems to involve mobilization of some transposable elements in plants (15), Drosophila (14,16), and pocket gophers (17). Any stressful conditions known to mobilize transposable elements, such as UV light, temperature, breeding conditions, etc.…”
mentioning
confidence: 99%
“…Repetitive DNA elements, including retro-transposons, are major components of eukaryotic genomes and such elements have a tendency towards amplification (Bennetzen and Kellogg 1997;Kalender et al 2000). Major decreases in genome size occur less frequently and such decreases have been observed especially following a doubling of the total genome by polyploidization (Ohri 1998), or the change from perennial to annual habit (Bennett 1972).…”
Section: Introductionmentioning
confidence: 99%